Identification and characterization of a novel legume-like lectin cDNA sequence from the red marine algae Gracilaria fisheri - Sukanya Suttisrisung (2018)
A legume-type lectin (L-lectin) gene of the red algae Gracilaria fisheri (GFL) was cloned by rapid amplification of cDNA ends (RACE). The full-length cDNA of GFL was 1714 bp and contained a 1542 bp open reading frame encoding 513 amino acids with a predicted molecular mass of 56.5 kDa. Analysis of the putative amino acid sequence with NCBI-BLAST revealed a high homology (30-68%) with legume-type lectins (L-lectin) from Griffithsia japonica, Clavispora lusitaniae, Acyrthosiphon pisum, Tetraodon nigroviridis and Xenopus tropicalis. Phylogenetic relationship analysis showed the highest sequence identity to a glycoprotein of the red algae Griffithsia japonica (68%) (GenBank number AAM93989). Conserved Domain Database analysis detected an N-terminal carbohydrate recognition domain (CRD), the characteristic of L-lectins, which contained two sugar binding sites and a metal binding site. The secondary structure prediction of GFL showed a β-sheet structure, connected with turn and coil. The most abundant structural element of GFL was the random coil, while the α-helixes were distributed at the N- and C-termini, and 21 β-sheets were distributed in the CRD. Computer analysis of three-dimensional structure showed a common feature of L-lectins of GFL, which included an overall globular shape that was composed of a β-sandwich of two anti-parallel β-sheets, monosaccharide binding sites, were on the top of the structure and in proximity with a metal binding site. Northern blot analysis using a DIG-labelled probe derived from a partial GFL sequence revealed a hybridization signal of ∼1.7 kb consistent with the length of the full-length GFL cDNA identified by RACE. No detectable band was observed from control total RNA extracted from filamentous green algae. © Indian Academy of Sciences.